Modeling the growth effects of regional knowledge production: The GMR-Europe model and its applications for EU Framework Program policy impact simulations - Attila Varga; Péter Járosi; Tamás Sebestyén (European Regional Science Association (ERSA), 2011)
This paper introduces the Geographic Macro and Regional (GMR) model for NUTS-2 regions of the Euro zone. This model consists of three blocks: the TFP, the SCGE and the MACRO blocks. The model is built for impact analysis of policies targeting intangible assets in the forms of R&D, human capital and social capital. The analysis can be done both at the regional and the EU macroeconomic levels. Policy simulations on the growth impacts of the 6th European Framework Program illustrate the capabilities of the complex model system.
Keywords: 330